How Much did Sri Lankans Move During Covid-19 Crisis? Community Mobility and Public Health Interventions in Retrospect - N. W. A. N. Y. Wijesekara; U. B. Wanigasekara; J. S. Wickramanayake (College of Community Physicians of Sri Lanka, 2021)
Introduction: During COVID-19 crisis, restricting the mobility of individuals was done through school, pre-school and university closure, work from home and imposing of curfew in Sri Lanka. Mobility of people is a proxy of social distancing interventions.   Objectives: To assess the mobility of Sri Lankans during COVID-19 crisis against the public health interventions implemented.   Methods: We obtained the Google Community Mobility Report (GCMR) data for Sri Lanka for six location categories, namely grocery and pharmacy, parks, transit stations, retail and recreation, residential and workplaces, and calculated a new category named 'Out of Home Locations' (OHL). Percentage deviation from the baseline (PDB) was calculated by considering the median value for a reference period of "same day of the week" as zero. Key public health interventions influencing mobility and COVID-19 cases by date were listed. Minimum and maximum PDB were calculated for the categories of locations. Trend lines with and cases were plotted against public health interventions Cross correlation function was used to assess any lagged relationship between the trends in GCMR and COVID-19 cases.   Results: All categories of locations except residential areas showed negative PDBs. The maximum negative PDB for grocery and pharmacy, retail and recreation, transit stations, workplaces and parks and recreation categories were 92, 88, 81, 79, and 59, respectively. In contrast, the residential area category showed the highest positive PDB of 47. There was a close relationship between the school, pre-school and university closure, work from home and imposing and lifting of curfew and the PDB trends. Even after the total release of curfew, the PDB at OHL and residential categories remain at - 20 and 10, respectively. Cross correlation function between GCMR and COVID-19 cases was not statistically significant at any lag.   Conclusions & Recommendations: Sri Lankans have considerably reduced OHL mobility during the COVID-19 crisis, in connection with the implemented public health intervention. GCMR is a versatile tool in monitoring community mobility in Sri Lanka. It is recommended to share district-wise GCMR for Sri Lanka for better planning and monitoring of public health interventions.